Use of Iranian Medicinal Plants Effective on Male Fertility Indices - Mahnaz Yavangi (Journal of Global Pharma Technology, 2016)
This systematic review article was conducted to report medicinal plants that are effective on male fertility indices. To conduct this review, search terms fertility or pregnancy combined with medicinal plants, herb, and phyto were used to retrieve relevant publications indexed in ISI, PubMed, and Iranian scientific databases. Escanbil, Fumaria parviflora L., Apium graveolens L., Achillea millefolium inflorescence, Urtica dioica L., Withania somnifera L., Phaleria macrocarpa, Satureja khuzestanica, Achillea millefolium, Malva sylvestris, Humulus lupulus L., Allium cepa, Petroselinum crispum, Carthamus tinctorius, and Zingiber officinale were reported to be medicinal plants with fertility indices-promoting properties. Medicinal plants that are used in Iran affect hormonal compounds and other effective compounds on hormonal system as well as the proliferation and viability of sex cells due to their antioxidant properties, and therefore enhance fertility in human and animals. Keywords: Physiotherapy, Infertility, Pregnancy, Iran.